2008
DOI: 10.1016/j.jmmm.2007.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance and spin-transfer torque in magnetic tunnel junctions

Abstract: We comment on both recent progress and lingering puzzles related to research on magnetic tunnel junctions (MTJs). MTJs are already being used in applications such as magnetic-field sensors in the read heads of disk drives, and they may also be the first device geometry in which spin-torque effects are applied to manipulate magnetic dynamics, in order to make nonvolatile magnetic random access memory. However, there remain many unanswered questions about such basic properties as the magnetoresistance of MTJs, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(64 citation statements)
references
References 96 publications
(141 reference statements)
2
62
0
Order By: Relevance
“…In an MFTJ, the carrier concentration and/or chemical bonding strength manipulations at the ferroelectric/ferromagnetic interfaces may give rise to an interfacial magnetoelectric effect, which can change the magnetic anisotropy, coercivity, or even the interfacial magnetic structure by an electric field through switchable ferroelectric polarization. [22][23][24][25] This strong interfacial magnetoelectric coupling in MFTJs provides an alternative energy-efficient route to manipulate spins by an electric field besides the spin transfer torque 26 and electric field assisted switching effects 27 in MTJs. Meanwhile, the interrelationship between ferroelectricity of the barrier layer and ferromagnetism of the electrodes through an interface magnetoelectric effect also affects the functional properties of TMR and TER in MFTJs.…”
Section: Introductionmentioning
confidence: 99%
“…In an MFTJ, the carrier concentration and/or chemical bonding strength manipulations at the ferroelectric/ferromagnetic interfaces may give rise to an interfacial magnetoelectric effect, which can change the magnetic anisotropy, coercivity, or even the interfacial magnetic structure by an electric field through switchable ferroelectric polarization. [22][23][24][25] This strong interfacial magnetoelectric coupling in MFTJs provides an alternative energy-efficient route to manipulate spins by an electric field besides the spin transfer torque 26 and electric field assisted switching effects 27 in MTJs. Meanwhile, the interrelationship between ferroelectricity of the barrier layer and ferromagnetism of the electrodes through an interface magnetoelectric effect also affects the functional properties of TMR and TER in MFTJs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with metallic spin valves, theoretical models [17,18,19] and experimental evidence [20,21] suggest that in magnetic tunnel junctions the spin torque is a function of voltage and does not depend on Z L (t), the time dependent device resistance, but only on R P . Therefore we assume that the spin torque in MTJ's is given by τ s =h 2e…”
Section: Resultsmentioning
confidence: 99%
“…where V (d, t) is the device voltage [17,18]. Although in general the torque can be a more complicated function of voltage, experiments have shown that at small bias the parallel torque is linear in voltage [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…The angular momentums may be transferred from the electrons of the spin-polarized current to the ferromagnet, giving rise to a switching of magnetization or stable precession of magnetizations [6] that leads to the generation of spin waves [7]. This mechanism of STT was initially proposed by Berger et al [8] and Slonczewski [9] in 1996 and attracted significant interests because of the great potential for direct current-induced spintronic devices [10][11][12]. The role of STT in magnetization switching has been verified by numerous experiments in spin-valve nanopillars [13][14][15], magnetic nanowires [16,17], point contact geometry [18][19][20], and magnetic tunnel junctions [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%